Alison Balter's mastering Access 2002 enterprise development - Balter, Alison (Sams, 2002)
Developing applications for the enterprise introduces challenges quite different from those associated with developing applications for desktops or small departments. This book offers a no-nonsense approach to enterprise development using Access 2002 as a front-end. it is written in a practical style and easily transitions the client/server neophyte to the sophisticated world of enterprise development. Although the book focuses on client/server development, the text covers other enterprise topics such as replication, trasaction processing, and data access pages. This book goes behond the basics covered by the many introductory books, but offers an easier read than the expert books available.